2019
DOI: 10.1021/acs.jpclett.9b02605
|View full text |Cite
|
Sign up to set email alerts
|

CsPbBr3 Perovskite Nanocrystal Grown on MXene Nanosheets for Enhanced Photoelectric Detection and Photocatalytic CO2 Reduction

Abstract: All-inorganic CsPbX3 (X = Cl, Br or I) perovskite nanocrystals have attracted extensive interest recently due to their exceptional optoelectronic properties. In an effort to improve the charge separation and transfer following efficient exciton generation in such nanocrystals, novel functional nanocomposites were synthesized by the in situ growth of CsPbBr3 perovskite nanocrystals on two-dimensional MXene nanosheets. Efficient excited state charge transfer occurs between CsPbBr3 NCs and MXene nanosheets, as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
208
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(216 citation statements)
references
References 43 publications
4
208
1
3
Order By: Relevance
“…In comparison, halide perovskite nanocrystals have large specific surface area and short carrier diffusion length, which may exhibit large potential in the field of photocatalysis application. [ 9,35–48 ] Encouragingly, in 2017, we for the first time reported a photocatalytic CO 2 reduction reaction by CsPbBr 3 QDs/graphene oxide composite in the non‐aqueous ethyl acetate reaction media. [ 9 ] Subsequently, various lead‐free perovskite nanocrystals including Cs 2 AgBiBr 6 , [ 19 ] Cs 2 PdBr 6 , [ 39 ] and Cs 4 CuSb 2 Cl 12 [ 40 ] with tunable band gap were synthesized to perform photocatalytic CO 2 reduction/photoelectrochemical cell application.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, halide perovskite nanocrystals have large specific surface area and short carrier diffusion length, which may exhibit large potential in the field of photocatalysis application. [ 9,35–48 ] Encouragingly, in 2017, we for the first time reported a photocatalytic CO 2 reduction reaction by CsPbBr 3 QDs/graphene oxide composite in the non‐aqueous ethyl acetate reaction media. [ 9 ] Subsequently, various lead‐free perovskite nanocrystals including Cs 2 AgBiBr 6 , [ 19 ] Cs 2 PdBr 6 , [ 39 ] and Cs 4 CuSb 2 Cl 12 [ 40 ] with tunable band gap were synthesized to perform photocatalytic CO 2 reduction/photoelectrochemical cell application.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. planted CsPbBr 3 NCs on 2 D MXene nanosheets by an in situ growth method . Efficient photodriven charge‐carrier transfer proceeds between CsPbBr 3 NCs and MXene nanosheets.…”
Section: Engineering Mhps For Photocatalysismentioning
confidence: 99%
“…It is reported that MXene nanosheets are abundant with surface terminations such as fluorine, oxygen, and hydroxyl groups, [ 29 ] which is inclined to interact with ligands such as OA and oleylamine. [ 30 ] These ligands will form kinetically favorable nucleation points for capturing PbBr 2 precursors. [ 19f,31 ] Thus the growth mechanism of MAPbBr 3 perovskite nanocrystals on MXene nanosheets could be elucidated as this: once the perovskite precursors (CH 3 NH 3 Br, PbBr 2 , OA, and OTA) were added into the Ti 3 C 2 T x suspension, OA/OTA will first interact with Ti 3 C 2 T x due to its abundant surface groups.…”
Section: Figurementioning
confidence: 99%
“…This phenomenon is commonly observed in previous reported perovskite NCs/2D nanosheets hybrid structures synthesized by solution growth method, where the PL lifetime is usually observed to decrease with more 2D nanosheets loaded in the synthesis. [ 19a,30 ] To make clear weather it is charge transfer or energy transfer in MAPbBr 3 /Ti 3 C 2 T x heterostructures, we first fabricated electron‐ and hole‐only photoelectric conversion devices [ 39 ] with MAPbBr 3 /Ti 3 C 2 T x heterostructures and pristine MXene as the active material. The device structures and corresponding photoresponse are shown in Figure S9 in the Supporting Information.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation